Development and acceptability of a novel milk‐free soybean–maize–sorghum ready‐to‐use therapeutic food (SMS‐RUTF) based on industrial extrusion cooking process. Issue 1 (29th March 2012) - Owino, Victor O.; Irena, Abel H.; Dibari, Filippo; Collins, Steve
Abstract: Peanut milk‐based ready‐to‐use therapeutic food (P‐RUTF) primarily used to treat severe acute malnutrition at community setting is expensive. We developed an alternative milk‐free soybean–maize–sorghum‐based RUTF (SMS‐RUTF) using locally grown ingredients that have the potential to support local economy and reduce the cost of RUTF. We describe the production process and results of acceptability of the new product. Acceptability and tolerance of SMS‐RUTF was compared with P‐RUTF among 45 children aged 4–11 years old based on a cross‐over design. Each child consumed 250 g RUTF for 10 days followed by a five‐day washout period and a subsequent 10‐day period on the second RUTF. The SMS‐RUTF was as acceptable as the P‐RUTF among normal children aged 4–11 years of age with no associated adverse effects. SMS‐RUTF was stable for at least 12 months without detectable microbiological or chemical deterioration. The major challenge encountered in SMS‐RUTF development was the difficulty to accurately determine key nutrient composition due to its high oil content. Use of diversified locally available ingredients to produce RUTF is feasible. The SMS‐RUTF meets expected standards and is acceptable to children aged 4–11 months old. Effectiveness and cost‐effectiveness of SMS‐RUTF is required.